2020
DOI: 10.4103/jehp.jehp_141_20
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hope and happiness with prenatal care

Abstract: INTRODUCTION: Prenatal care refers to proper and principled implementation aimed at maintaining a healthy pregnancy in terms of physical health and favorable psychological outcomes for the mother, infant, and family. The adequacy of prenatal care is an important indicator in predicting infant and maternal mortality. Mental health components such as hope and happiness can influence the quality of prenatal care. The aim of this study was to determine the relationship between hope and happiness with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…Babies are more likely to have greater levels of self-esteem and self-control when expecting moms feel content and at peace. 12 Pertinent fears about the progress of pregnancy, labour, and birth can be alleviated by physical, mental and emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…Babies are more likely to have greater levels of self-esteem and self-control when expecting moms feel content and at peace. 12 Pertinent fears about the progress of pregnancy, labour, and birth can be alleviated by physical, mental and emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to ensure that included studies comprehensively assessed RNT, we excluded studies in which RNT was only measured by a subscale of a questionnaire which indexed a broader construct (e.g., distress: Caparros-Gonzalez et al, 2019; feelings about one's infant: Furman & O'Riordan, 2006), or that measured RNT as one of a range of emotion regulation strategies (e.g., Ghorbani-Marghmaleki et al, 2019). That is, eligible studies needed to include a standalone measure of RNT.…”
Section: Literature Search Strategymentioning
confidence: 99%
“…Though far less studied than negative prenatal feelings, positive feelings during pregnancy, including feelings about the pregnancy, birth, and transition to motherhood, are associated with a range of beneficial outcomes from better maternal mental health and fetal growth to infant and child outcomes (Amiel Castro et al, 2020; DiPietro et al, 2002; Dipietro et al, 2008; McManus et al, 2017; Yali and Lobel, 2002). Pregnant women who feel more positive and hopeful are more likely to obtain prenatal care (Hoseini et al, 2020), breastfeed after birth (McManus et al, 2017), and have infants with fewer sleep problems (Liu et al, 2020). A recent study of almost 3400 mother–child dyads found that the more positive women felt during pregnancy, the less likely their children were to have a mental or behavioral disorder diagnosis from birth to 12 years of age (Lähdepuro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…stress, depression, anxiety) while pregnant appear to be detrimental to women and their offspring (Bedaso et al, 2021; Braithwaite et al, 2015). Conversely, positive feelings (hope, happiness, purpose) tend to be beneficial to women and children (Golmakani et al, 2012; Hoseini et al, 2020). However, feelings specific to the pregnancy, especially how the pregnancy is perceived as uplifting or a hassle have unique risks and benefits (Amiel Castro et al, 2020; McManus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%